Mnltitask Anti-Dust Cleaner - Rosli, Mohd Zaki AI Hafiz (Universiti Teknologi Petronas, 2008)
This report basically discusses the progress research done and basic understanding of the chosen topic, which is Multitask Anti-Dust Cleaner. The objective of this project is to introduce a new method in cleaning the SMT facilities especially in electronic production line. Nowadays, most of the electronic company use an air gun to blow the dust from the SMT devices. But, this new method, it use a concept of suctions technique rather than blowing method. The challenge of this project is to determine the suitable material to build up the prototype and the way to testing the prototype. The testing should be done in order to determine the suitable materials that need to use and the functionality of the prototype. This report also contains the materials selection for this project and some materials analysis. The analysis mostly bases on the characteristics of the material and its behavior. The analysis based on the literature review of this project. The aim of this project is to introduce a new cleaning method and increase worker efficiency and increase the productivity. Other than that, by done this project, the dust problem in production area can be reduce. When the project was done, hopefully the aim can be achieved.